2015
DOI: 10.15386/cjmed-497
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric color evaluation of permanent incisors, canines and molars. A cross-sectional clinical study

Abstract: Background and aimsAn accurate color reproduction represents the final validation level of an esthetic anterior or posterior restoration. The aim of this study was to evaluate the color of permanent maxillary incisors, canines and molars, using a clinical spectrophotometer.MethodsThe Vita Easyshade Advance 4.0® intraoral spectrophotometer was used by one clinician to determine the color of 369 permanent maxillary incisors, canines and molars. The best matches to Vitapan Classical® and 3D-Master® shade guides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 37 publications
1
44
0
4
Order By: Relevance
“…Many studies have been conducted on the measurement and distribution of tooth color, and researchers have used both conventional and digital methods in their tooth color determinations . Digital devices can provide a standard measurement of the tooth and are more reliable .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have been conducted on the measurement and distribution of tooth color, and researchers have used both conventional and digital methods in their tooth color determinations . Digital devices can provide a standard measurement of the tooth and are more reliable .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was reported that the black and grey backgrounds simulated the conditions of the mouth better during color measurements . Other studies have made direct measurements without using any colors in the background . In our study, the anterior tooth color measurements were performed using a grey background to better simulate the oral condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations